Peningkatan Kemampuan Representasi Matematis melalui Pendidikan Matematika Realistik pada Konsep Pecahan di Sekolah Dasar Negeri 1 Sibreh - Hayatunnizar Hayatunnizar (Didaktik Matematika, 2016)
Various attempts have been made to overcome the difficulties students learn mathematics. One is to apply Realistic Mathematics Education (Pendidikan Matematika Realistik/PMR). PMR can potentially improve the ability of students mathematical representation, including fraction. This study used a qualitative approach with classroom action research. The goal is to understand the mathematical representation ability of fourth grade students at SDN 1 Sibreh, Aceh, through PMR for fraction topic. This research was conducted in two cycles. The participants were 4 students-one student was high rank (S1), two students were midle rank (S2 and S3), and one student was low rank (S4). The data collected in this study includes process and outcome. Data collection instruments include students worksheets, the observation sheet and test sheet. The results of this study were (1) The percentage of the average score of students and teachers activities that are good categories in both the first cycle and the second cycle. (2) The percentage of students mathematical representation ability increased from 77% in the first cycle to 82% in the second cycle. It can be concluded that learning through Realistic Mathematics can improve the students mathematical representation ability about at grade IV SDN 1 Sibreh.